ANALISIS FAKTOR FAKTOR PENERIMAAN PAJAK DAERAH KABUPATEN KUBURAYA - Friani, Desi; Nazarudin, Nazarudin; Agustini, Yetty (Jurnal Ekonomi Integra, 2025)
This analysis was conducted to see whether there was an increase in regional tax revenue, the realization from year to year will increase according to existing factors. The study used a qualitative descriptive method, which provides an overview of the object being studied at the present time based on existing facts. Using primary data sources and secondary data with data collection techniques in the form of interviews and documentation. The location is in Kubu Raya Regency at the Regional Revenue Agency located at Jalan Supadio, Arang Limbung, Kec. Sungai Raya, Kubu Raya Regency, West Kalimantan. Regional tax revenue for Kubu Raya Regency has not reached the target, namely the swallow's nest tax and groundwater tax, one of them. Factors that inhibit regional tax revenue are economic downturn, declining purchasing power of the community, and changes in local/national policies. The study aims to determine the Factors That Influence Regional Tax Revenue at the Kubu Raya Regency Regional Revenue Service, and to determine supporting factors, regional tax revenue, factors inhibiting regional tax revenue